Re-examining the testing effect as a learning strategy: the advantage of retrieval practice over concept mapping as a methodological artifact - Mayrhofer, Roland; Kuhbandner, Christof; Frischholz, Katja (Frontiers in Psychology, 2023)
Several previous studies appear to have demonstrated that studying with retrieval practice produces more learning than studying with concept mapping, a finding based on which an extended use of retrieval practice in educational practice was recommended. However, a closer examination of the methods used in these previous studies reveals a crucial confounding variable: Whereas participants in the concept mapping conditions performed a concept mapping task without any subsequent memorizing of the learning material, participants in the retrieval practice conditions performed not only retrieval practice but also an additional memorization task, which doubled the total memorization time. The present preregistered study examined whether the advantage observed in the retrieval practice condition over the concept mapping condition in previous studies was actually driven by additional memorization rather than by retrieval practice. While we replicated the previous finding that retrieval practice in combination with additional memorizing produces more learning than concept mapping without additional memorizing, this advantage of retrieval practice over concept mapping vanished when participants in the concept mapping condition, too, memorized the learning material after having created a concept map. These findings demonstrate that the assumed advantage of retrieval practice over concept mapping in fact represents a methodological artefact. Besides serving as a reminder of the importance of a solid methodology, the present study also illustrates the importance of using of an adequate terminology. Depicting a learning strategy condition as "retrieval practice" when the condition actually encompasses not only retrieval practice but also additional memorizing obfuscates the possibility that observed memory advantages may not be fueled by retrieval practice, i.e., the learning strategy as such. We conclude by giving an outlook over at the ramifications of our findings for cognitive and educational psychology.